Structural Analysis of Nanoceria Powder Precipitated in Different pH - Iis Nurhasanah; Nurul Wahyu Puspaningrum; Ida Nursati (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
Nanoceria has been proposed as inorganic material for sunscreen product because of its excellent UV absorpsition ability. Fine particle nanoceria and non-aglomeration determines comport and covering capability on human skin. Particle size and aglomeration could be controlled by parameters and medium synthesis. In the present work, nanoceria powders were synthesized using precipitation method in different pH of 7 and 10. Precipitation was cariedout in water/isopropanol mixed solvent. Cerium nitrate and amonium hydroxide was used as source of cerium and precipitation agent, respectively. Crystal structure of nanoceria was examined using x-ray diffraction (XRD). Scanning electron microscope (SEM) was used to observe morphology of nanoceria. Diffraction pattern analysis shows that the precipitates were single phase of nanoceria with cubic fluorite structure and lattice contants of 0.5429 nmand 0.5419 nm. Crystallite size and lattice strain were obtained from Williamson-Hall method. Precipitation in pH of 7 resulted in smaller crystallite size which correlated to the larger lattice strain and lattice constant. SEM image shows spherical morphology with less agglomeration occuring for nanoceria precipitated in pH 10.